Key Contract Management Issues and Recommendations on IT Outsourcing in Taiwanese Hospitals - Lin, Chad; Huang, Y.; Li, C.; Jalleh, Geoffrey (National Changhua University of Education, 2011)
All organizations including hospitals have goals and objectives, regardless of size. To achieve these goals and objectives, hospitals have to outsource some of their information technology (IT) functions. There is no guarantee that IT outsourcing will be perceived as successful due to the very different expectations held by the various stakeholders. However, the contract management process of IT outsourcing in hospitals is particularly under-studied. Hence, the major objective of this paper is to identify and examine key IT outsourcing contract management issues in Taiwanese hospitals. Based on our data, recommendations are provided to deal with the identified key issues that are crucial in managing IT outsourcing contracts in Taiwanese hospitals.